Diplomacy and International Economic Relations. The Presidential Meeting Between Perón and Ceauçescu (1974) - Miguez, Maria Cecilia (Revista de Historia Social y de las Mentalidades, 2024)
This paper examines the diversification of international relations during the third Peronist government, focusing on Nicolae Ceaușescu’s 1974 visit to Argentina. During this visit, several agreements were signed to strengthen bilateral ties. The study aims to assess the impact of this event across various dimensions framed within Peronism’s broader efforts to diversify its international ties. The analysis draws on multiple sources, including newspaper articles, classified and declassified official documents from the Archive of the Argentine Foreign Ministry (AMREC), and materials from the Gerald Ford Presidential Library in the United States.